2021
DOI: 10.3390/pathogens10050522
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Properties of GI-23 Infectious Bronchitis Virus Isolated in Poland and Efficacy of Different Vaccination strategies

Abstract: Infectious bronchitis virus (IBV) is one of the most important poultry pathogens, leading significant economic losses worldwide. IBV is characterised by highly genetic, serotype, and pathotypic variability. Despite extensive immunoprophylaxis strategies, the emergence of new genetic lineages is frequently observed in the field, causing disease control to be more complicated. In the last decade, the spread of variants assigned to the GI-23 lineage of IBV (formerly known as Var2) started from Middle-Eastern coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…Lesions observed in the lungs occurred inconsistently, being present in only a few birds and, to a mild degree, agreeing with Lisowska et al (2021) [ 37 ]. Our trials have shown that IBV rarely causes lung damage.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Lesions observed in the lungs occurred inconsistently, being present in only a few birds and, to a mild degree, agreeing with Lisowska et al (2021) [ 37 ]. Our trials have shown that IBV rarely causes lung damage.…”
Section: Discussionsupporting
confidence: 88%
“…Zanaty et al (2016) [ 36 ] concluded that the most severe clinical symptoms of IBV appear in very young chicks and the severity decreases in older chickens. Lisowska et al (2021) [ 37 ] agree with that, summarizing that the pathogenicity of GI-23 is more severe in young birds. To Awad et al (2016) [ 38 ], the disease was of a lesser severity in broilers compared to SPF chicks, reflecting the inhibitory effects of the IBV maternal antibodies or genetic/strain susceptibility, or both.…”
Section: Discussionmentioning
confidence: 75%
“…GI‐23 seems to have initially disseminated in the Middle Eastern countries and after reached Europe and Africa in the last decade (Houta et al., 2021). Due to the important economic losses to the poultry industry, different vaccination programmes have been developed for this lineage (Abozeid & Naguib, 2020; Lisowska et al., 2021). The present study aimed to describe the emergence and molecular characteristics of GI‐23 strains recently detected in Brazil (the first report in South America) as well as the rapid spread in commercial broiler farms in the southern region of the country.…”
Section: Introductionmentioning
confidence: 99%
“…A decline followed the intense rise, probably due to effective control measures implementation and crescent population immunity. A second major peak was observed after GI-23 viruses introduction to Europe, where a naïve host population was present, and the implementation of specific vaccination strategies was limited and tardive, or even totally absent [ 30 , 49 ]. Additionally, more intense diagnostic sequencing activity in European countries likely contributed to an overrepresentation of available sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, European poultry populations are mainly vaccinated with a combination of Mass plus 793B or Mass plus QX vaccines to protect against the highly prevalent QX field strains [ 49 ]. Although cross-protection was demonstrated experimentally, this issue deserves to be further investigated as it is unclear whether these vaccinations display a limited efficacy against GI-23 in field conditions or if a difference exists between the protocols that could justify the expansion of GI-23 in Europe [ 45 , 49 ].…”
Section: Discussionmentioning
confidence: 99%